The role of sports media in promoting the ethics of sports professionalism - ben djamaa, sif islem (sports creativity, 2025)
The media, in general, acts as a mirror to the society whose events it covers, attempting to reveal the true dimensions of all its aspects, pivotal points, and details. This is especially true given the transformation of sports, with modern developments, into a major social phenomenon and one of the economic drivers in the developed world. Money has become dominant in the sports world, as it has shifted from mere hobby and enjoyment to professionalism, generating enormous sums of money for its practitioners, amounting to millions from all corners of the globe. French economic expert Jean-François Bourges confirmed that the global revenue of sports is now estimated at $400 billion, including $4.3 billion for football alone. Thus, sports have become an economic activity, just like other sectors. This explains the abandonment of Olympic principles and the reorganization of this field around new commercial values. This financial expansion would not have been possible without the media, which experienced a significant boom in the field with the spread of satellite broadcasting. Television has become a major consumer of sports programming, generating substantial revenue. Sports heroes are turned into stars used in advertisements, and some - unfortunately - bet on players and on match results, which means that market economics has invaded the world of sports, which has therefore become completely detached from any human or moral value, and entirely subject to the mechanisms of the market, supply and demand.